Applying SPHINX-II to the DARPA Wall Street Journal CSR task - Alleva, Fil; Hon, Hsiao-Wuen; Huang, Xuedong; Hwang, Mei-Yuh; Rosenfeld, R.; Weide, Robert (HLT '91 Proceedings of the workshop on Speech and Natural Language, 1992)
This paper reports recent efforts to apply the speaker-independent SPHINX-II system to the DARPA Wall Street Journal continuous speech recognition task. In SPHINX-II, we incorporated additional dynamic and speaker-normalized features, replaced discrete models with sex-dependent semi-continuous hidden Markov models, augmented within-word triphones with between-word triphones, and extended generalized triphone models to shared-distribution models. The configuration of SPHINX-II being used for this task includes sex-dependent, semi-continuous, shared-distribution hidden Markov models and left context dependent between-word triphones. In applying our technology to this task we addressed issues that were not previously of concern owing to the (relatively) small size of the Resource Management task.